English Teachers’ Beliefs in Teaching English Grammar to Improve Students’ Speaking Skill - Karisma Erikson Tarigan; Margaret Stevani (Journal of English Language and Education, 2022)
English teachers’ beliefs had an important role in their decision-making about how grammar should be taught. Approaches to foreign grammar pedagogy were informed not only by the point of view of grammar, but also by beliefs about the importance of grammar, how it could be learned, and how it could be taught. The aims of teaching English grammar in this research were to know the factors that could influence English foreign language teachers’ beliefs in English grammar teaching and their roles in the practice of teaching English grammar. A mixed-method that involved qualitative and quantitative methods in this research was used to describe any insight of English teachers in teaching English grammar. The data were collected based on a close-ended interview and a questionnaire administered to 27 English teachers in 3 junior high schools and 3 senior high schools in North Sumatra, Indonesia. The results showed that: (1) the reasons for the importance of grammar teaching in speaking skills, (2) the way how grammar should be taught in speaking skills, (3) the techniques to teach English grammar, (4) the challenges of teaching grammar in speaking skills, and (5) the procedures to teach English grammar. This research recommended English teachers reflect on the professional and pedagogical contexts of English grammar teaching to improve the quality of English teachers’ teaching behaviors.